2016
DOI: 10.3354/cr01393
|View full text |Cite
|
Sign up to set email alerts
|

Changes in temperature extremes for 21st century scenarios over South America derived from a multi-model ensemble of regional climate models

Abstract: This study examines a set of 4 temperature extreme indices (cold and warm nighttime and daytime indices) from an ensemble of 4 regional climate models (RCMs) for present and future periods in South America (SA). These models were integrated in the framework of the CLARIS-LPB 7FP-EU-project. We analyze the capability of RCMs to reproduce such indices and explore changes projected by the models under the scenario A1B for the end of the 21st century. The work also analyzes the role of cloudiness, surface radiativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 54 publications
3
15
0
1
Order By: Relevance
“…The reliability of the projected changes from RCMs may also be built after assessing the extent to which models are able to represent present climate conditions. Several studies have focused on assessing the reliability of regional climate models over the Andes and most of them found that RCMs usually present systematic biases, such as an underestimation of temperature at different altitudes (López-Franca et al, 2016) and a overestimation of precipitation over the mountains, in particular over the eastern Andes slopes (Solman and Blazquez, 2019; see Figure 2a in Menéndez et al, 2016). The origin of these biases lies, at least partly, in unresolved topographical forcing which remains too smoothed over the complex terrain of the Andes, limiting the simulation of regional processes such as the interactions between local circulation and orography, a key factor in climate modulation at meso-scale levels.…”
Section: Regional Climate Downscalingmentioning
confidence: 99%
“…The reliability of the projected changes from RCMs may also be built after assessing the extent to which models are able to represent present climate conditions. Several studies have focused on assessing the reliability of regional climate models over the Andes and most of them found that RCMs usually present systematic biases, such as an underestimation of temperature at different altitudes (López-Franca et al, 2016) and a overestimation of precipitation over the mountains, in particular over the eastern Andes slopes (Solman and Blazquez, 2019; see Figure 2a in Menéndez et al, 2016). The origin of these biases lies, at least partly, in unresolved topographical forcing which remains too smoothed over the complex terrain of the Andes, limiting the simulation of regional processes such as the interactions between local circulation and orography, a key factor in climate modulation at meso-scale levels.…”
Section: Regional Climate Downscalingmentioning
confidence: 99%
“…Third, how to choose the competent model from the intended model sets to successfully fulfill the research tasks is another key challenge. In addition to the wills of the modelers, applicability of such models to specific targeted problems is also a crucial consideration of model options, including solidifying model structures, data availability at the micro level, and solving feasibility, especially for IAM-based MMC frameworks and non-IAM multi-model ensemble analysis (Tavoni et al 2014, Zhang et al 2015, Lopez-Franca et al 2016, Romera et al 2017.…”
Section: Insights For Future Multi-model Studymentioning
confidence: 99%
“…Other possible factors that influence the daily Tmax over LPB, such as cloud cover and surface radiative forcing, were discussed by López‐Franca et al . (). They showed that an ensemble of RCMs was able to capture the role of cloudiness in decreasing Tmax during the daytime by reflecting solar radiation.…”
Section: Discussion and Summarymentioning
confidence: 97%
“…() and Solman () for summer mean temperature and López‐Franca et al . () for seasonal mean of maximum temperature. Carril et al .…”
Section: Discussion and Summarymentioning
confidence: 99%
See 1 more Smart Citation